Implementasi Media Flash Card Untuk Meningkatkan Kemampuan Membaca Pada Anak Usia Dini - Alifah Fuji Yanthi Anisa; Naila Attamimi (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2023)
The purpose of this study was to develop reading skills in children, as well as a means of teaching and learning between students and teachers with Flash Card media for students aged 5-6 years at RA Bani Sya'I, Paku Haji Tangerang. This research was made through several phases of observation and data collection. First, observe the process on the existing phenomena. The second is field observation or during the direct learning process at RA Bani Sya'i. In the process of collecting data there are several processes, including: Questionnaires, Interviews, and Literature Research. The processes of research and data collection through a qualitative approach which emphasizes the analysis more on the process of deductive inference, as well as inferring the relationship between the phenomena of the existing problems. The results of the research on the implementation of Flash Card media show that there are still many students who have poor reading and letter recognition skills. And with the application of the Flash Card media learning method to students in the classroom, students' abilities become better in the context of reading and recognizing letters. The purpose of this study is the application of Flash Card Media to improve reading skills in children aged 5-6 years at RA Bani Sya'I, Paku haji subdistrict.